PENGGUNAAN KUARTET PROKLAMASI TERHADAP OPTIMALISASI PEMBELAJARAN IPS PADA CRITICAL THINKING SISWA PENDIDIKAN DASAR - Anggraini, Amelia; Fathoni, Achmad (STIT AL MULTAZAM, 2023)
Critical thinking is the competence to evaluate the quality of a source of information as well as recognizing existing viewpoints and evaluating the evidence used to support a view. This study aims to determine how the use of proclamation quartet game cards can optimize students' critical thinking skills in learning social subjects. The research method is quantitative with a pretest-posttest design for one group. Before data analysis, a normality test was conducted using the Shapiro-Wilk method. After that, data analysis was carried out using the Dependent Parametric Statistical Test (t-Test)/Paired Sample t-Test. The findings of this study, namely the output of the t-test results obtained a sig value = 0.000 which is smaller than 0.05, meaning that it supports the alternative hypothesis. It was also evidenced by the average pretest result of 53.33 which increased to 81.56 in the posttest. The implications of using proclamation quartet cards include students' ability to make predictions, find solutions, evaluate, and draw appropriate conclusions. Although it takes time, interactivity, and increased student memory make proclamation quartet cards an effective tool in optimizing history learning and students' critical thinking competencies.